A new subspecies of Crepidium commelinifolium (Malaxideae; Epidendroideae; Orchidaceae) - Margonska, Hanna B (Phytotaxa, 2015)
Crepidium commelinifolium (Zollinger & Moritzi in Zollinger 1844: 402) Szlachetko (1995: 125) belongs to sect. Commelinodes (Schlechter 1911: 124) Szlachetko (1995: 123), subsect. Commelinodes (Margońska & Szlachetko, 2010: 4) and occurs mainly in Java but also in Borneo (Malaysia, Brunei, Indonesia), at elevations ranging from 200–2,000 m above sea level. This terrestrial orchid species forms colonies that are sometimes dense and cover relatively large areas, but it always occurs in shaded to deeply shaded locations that are moist or wet. Owing to its occurrence at a wide range of altitudes and on various substrates etc., it came as no surprise that this species shows variation. For years, I have observed plants of this species produce leaves of two kinds. In most plants, including the type-specimens, the leaves are almost cordate to ovate, shortly attenuate, acute, with a cordate base and simple, entire margins. A second group of plants, however, possesses oblong-ovate to ovate-lanceolate leaves with undulate margins. I have never observed populations of both groups occurring at the same location. Nevertheless, both groups are well represented in herbarium collections, both as dried, pressed specimens and as liquid–preserved material.